Slow Pyrolysis of Biowastes: Environmental, Exergetic, and Energetic Assessment - Zalazar García, Daniela Inés Yanina (2022)
Slow pyrolysis of a pellet of pistachio waste was studied using a lab-scale stainless-steel reactor. Experiments were conducted at different heating rates (5, 10, and 15 K/min). A 3-E (environmental, exergetic, and energetic) analysis for the processing of 20 kg/h of biowaste was carried out. Experimental results showed that biochar and gas yields decreased with an increase in the heating rate (43% to 36% and 28% to 24%, respectively), while the bio-oil yield increased (29% to 40%). Finally, from the 3-E analysis and the experimental results, it can be suggested that an increase in the heating rate resulted in a higher pyrolysis exergetic efficiency (70%), due to an increase of the bio-oil yield with high-energy content.